2019
DOI: 10.1016/j.physbeh.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyphenol (carob) supplementation on body composition and aerobic capacity in taekwondo athletes

Abstract: Herbal products and supplements use by athletes has increased over the past decade. One such item being polyphenols. These are reported to reduce weight and modify body composition, which could aid athletes in many sports. Therefore, the purpose of the study was to determine the effect of 6 weeks supplementation with carob, a naturally occurring polyphenol, on body composition and aerobic capacity in youth taekwondo athletes. Twenty-three taekwondo athletes (21.9±1.2 years; 1.64±0.03m; 67.4±17.3kg;BMI: 22.8±5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 55 publications
1
37
0
8
Order By: Relevance
“…A previous study demonstrated that oral polyphenol supplementation is a critical sports nutrition strategy to facilitate mitochondrial biosynthesis for athletes to delay the onset of exercise fatigue and to enhance performance [13,14]. Resveratrol (RES), as a nutritional supplement, is a natural polyphenol compound accompanied by functions of increasing antioxidant activity [15], anti-inflammation [16], anti-aging [17] and diabetes prevention [18].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that oral polyphenol supplementation is a critical sports nutrition strategy to facilitate mitochondrial biosynthesis for athletes to delay the onset of exercise fatigue and to enhance performance [13,14]. Resveratrol (RES), as a nutritional supplement, is a natural polyphenol compound accompanied by functions of increasing antioxidant activity [15], anti-inflammation [16], anti-aging [17] and diabetes prevention [18].…”
Section: Introductionmentioning
confidence: 99%
“…Its dynamics allows predicting the growth of sportsmanship. In the work of Gaamouri et al [22] control of body weight and somatotype components was used to assess the effectiveness of the use of dietary supplements. A similar approach was used by Martinelli et al [23] to assess the status of taekwondo athletes in the pre-competition period and during post-competition recovery.…”
Section: Discussionmentioning
confidence: 99%
“…[8] [9] [10] [11] [4]. Any sport requires a certain type of physical fitness, including the martial arts sports taekwondo and karate [12] [13]. Taekwondo martial arts is a modern sport that has its roots in Korean traditional martial arts which consists of three important materials, namely poomse, kyukpa, kayoruki.…”
Section: Introductionmentioning
confidence: 99%